GROUP THERAPY FOR HIGH-CONFLICT DIVORCE the 'no kids in the middle' intervention program. - Visser, Margreet; Lawick, Justine van ([S.l.] : ROUTLEDGE, 2021)
The "No Kids in the Middle" (Kinderen uit de Knel) intervention programme addresses high-conflict divorce through a multi-family approach. This first English language edition contains descriptions of the therapeutic sessions, references to a homework book (van der Est et al.) for parents and their network, along with extra information about the theoretical foundations of the programme. The book starts with theoretical foundations and a summary of the scientific research behind the methodology before moving on to focus on the methodology of the intervention programme per session, with detailed descriptions of each therapeutic session. Through these session descriptions, the authors demonstrate how the theory of the methodology can be put into practice within a group setting. The methodology is also conveyed in such a way that the key pillars and themes are clear, with a best-practice framework clearly demonstrated. Yet at the same time, the authors leave room for customization depending on the actual clients and therapists, and for this framework to be built upon further. With this programme now practiced and studied throughout Europe, Group Therapy for High-Conflict Divorce and its methodology will act as a living framework to help continuously improve practice and research among professional therapists, while also appealing to social workers and legal professionals.
OCLC-licensed vendor bibliographic record.
Keywords: Family psychotherapy; Divorce -- Psychological aspects; Custody of children; Domestic relations; PSYCHOLOGY / Mental Health; PSYCHOLOGY / Psychotherapy / Couples & Family